Chapter Does an entrepreneurial spirit animate fresh graduates in their work-seeking during uncertain times? - Fabbris, Luigi (Proceedings e report, 2021)
The labour market is becoming harder and harder even for graduates. The economic difficulties added by Covid-19 restrictions worsened the graduates' employability. In our opinion, public authorities should intervene to soften the school-to-work transition and graduates should become more entrepreneurial to overcome own market difficulties. We realised a survey on graduates from Padua University, the largest university in the Veneto region, Italy. In this survey, among other things, the entrepreneurial spirit of graduates was investigated. This spirit is intended as both the propensity to undertake an own business and the skill to find own ways and resources to overcome the possible difficulties while searching for a job either as employee or self-employed. It emerged that the propensity to start an own business concerns only a bunch of fresh graduates and that the capacity to implement personality resources is large among young people but remains unexplored because of cultural and contingent reasons.